Lieux de culte, vegetation, ancetres, en Indonesie de 1'Est : qui protege et qui est protege? - Claudine Friedberg; Y. Purwanto; Dyah M. Suharno; Eko B. Walujo (The Ethnobiological Society of Indonesia, 2004)
This article discusses knowledge and local wisdom of the East Indonesian societies specially Bunag and Dawan society in (Nusa Tenggara Timur/ West Timor), Dani society in Baliem valley (Irian Jaya) and Alune society at Lumoli (Seram, Moluccas). Furthermore, it covers their knowledge and wisdom of natural resources, particularly the relation of the natural sacred site to natural resources. The existence of natural sacred site and various rituals activities related to their effort in order to protect plants natural resources, and it has played an important role in protecnng and conserving plant natural resources. The knowledge and local wisdom of these societies and their role in plant diversity conservation will be discussed completely in this article.